Segurança jurídica e garantismo na nova sistemática de identificação, processamento e julgamento de atos de improbidade administrativa - Nascimento, Bruna Barbosa de Góes (2023)
The legal uncertainty brought about by the administrative improbity law in its original wording, with the scope given to undetermined legal principles and concepts in the context of current neoconstitutionalism, raised the need for a better legal delimitation of its typology, the redefinition of its subjective element and the structuring of the due legal process applicable to its processing. Legal certainty was reinforced with the wording of Law No. 14,230/2021, which expressly provided for the application of the system of sanctioning administrative law to the facts under its regency. The dissertation seeks to relate this intent of legal certainty with criminal guaranteeism, expressly referred to in the aforementioned legislation. The hypothesis of the work presented is that Law n. º 14.230/2021 brought considerable gains in terms of applicability and legal certainty by expressly identifying the judicial prosecution of acts of impropriety as subject to the regime of sanctioning administrative law. Similarly, consensus, established under the terms of the new wording, with an express provision and outline of requirements for the conclusion of the civil non-prosecution agreement, will be presented as representative of gains in terms of respect for due legal process in a guaranteeing perspective. Therefore, the dissertation will present the main innovations brought in the current system, relating theory and practice, facing the most up-to-date jurisprudence on the subject, as well as the possible effects they may have.